An assessment of mosquito collection techniques for xenomonitoring of anopheline-transmitted Lymphatic Filariasis in Ghana. Issue 13 (14th June 2018) - Opoku, Millicent; Minetti, Corrado; Kartey-Attipoe, Worlasi D.; Otoo, Sampson; Otchere, Joseph; Gomes, Bruno; de Souza, Dziedzom K.; Reimer, Lisa J.
Abstract: Monitoring vectors is relevant to ascertain transmission of lymphatic filariasis (LF). This may require the best sampling method that can capture high numbers of specific species to give indication of transmission. Gravid anophelines are good indicators for assessing transmission due to close contact with humans through blood meals. This study compared the efficiency of an Anopheles gravid trap (AGT) with other mosquito collection methods including the box and the Centres for Disease Control and Prevention gravid, light, exit and BioGent-sentinel traps, indoor resting collection (IRC) and pyrethrum spray catches across two endemic regions of Ghana. The AGT showed high trapping efficiency by collecting the highest mean number of anophelines per night in the Western (4.6) and Northern (7.3) regions compared with the outdoor collection methods. Additionally, IRC was similarly efficient in the Northern region (8.9) where vectors exhibit a high degree of endophily. AGT also showed good trapping potential for collecting Anopheles melas which is usually difficult to catch with existing methods. Screening of mosquitoes for infection showed a 0.80–3.01% Wuchereria bancrofti and 2.15–3.27% Plasmodium spp. in Anopheles gambiae . The AGT has shown to be appropriate for surveying Anopheles populations and can be useful for xenomonitoring for both LF and malaria.